A Qualitative Descriptive Study on the Benefits of Painting and Puzzles for Children in Broken Homes at PYI TMP Taruna Tangerang City - Wardhani, Vadia Hijriyah (Raudhah Publisher, 2024)
This research is that there is still a widespread negative perception among the general public about children born to broken homes. The general public still holds the misconception that children born into broken homes are unmanageable and wild. The purpose of this study is to issue the benefits of painting and puzzles for foster children at PYI TMP Taruna in Tangerang City. This study uses descriptive research with a qualitative approach. Details of the data collection method through observation and interviews. The data analysis technique uses the Miles and Huberman model, namely data collection, data reduction, data presentation and conclusion drawn. The subjects of this study were 2 children in broken homes aged 8-12 years. The results of this study show that foster children at PYI TMP Taruna are able to regulate their attitudes and emotions, as well as be more confident and can develop their talents through painting and puzzles.